2001
DOI: 10.1598/rrq.36.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Identity Construction in Elementary Readers and Writers

Abstract: S By examining the perspectives of students and others close to them, this study of 12 fifth graders from diverse backgrounds explores the role of literacy and curriculum in identity construction. Data collection included interviews with students, parents, the teacher, and peers; classroom observations; and analyses of student writing. Analyses of the data suggested that there was coherence of perspectives about six of the students while there was less agreement for six other students; perspective and context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 21 publications
1
46
0
3
Order By: Relevance
“…Because learning is mediated through social interaction, student success and interest in literacy is dynamic and dependent on diverse contexts and partners, such as school peer groups, friendship groups, and family (McCarthy, 2001). Just as the participants in the study of Sanford and Blair (2004) developed literacy through guided peer participation in informal settings, Nicholas benefited from social interaction and tasks that were scaffolded in multiple contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Because learning is mediated through social interaction, student success and interest in literacy is dynamic and dependent on diverse contexts and partners, such as school peer groups, friendship groups, and family (McCarthy, 2001). Just as the participants in the study of Sanford and Blair (2004) developed literacy through guided peer participation in informal settings, Nicholas benefited from social interaction and tasks that were scaffolded in multiple contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Gee and Crawford (1998) stated that we can take on different identities, depending upon the social setting, yet there are relationships between these identities. Continuing the metaphor, it can be concluded that the better the relationships between the different identities, the better the chorus of voices sounds (see also McCarthey, 2001).…”
Section: Definition Of Professional Identitymentioning
confidence: 99%
“…The survey instrument was created by the researchers using current literature on literacy identity (Gee, 2006;McCarthey, 2001;Moje & Luke, 2009). The instrument was shared with three reviewers with expertise in literacy and/or identity research and revised based on their feedback in order to increase the content validity.…”
Section: Data Collectionmentioning
confidence: 99%
“…The semi-structured interview questions were grounded in literacy identity research (Gee, 2006;McCarthey, 2001;Moje & Luke, 2009) and sought to explore the relationship between participant's literacy histories and their literacy identities. The interviews ranged from 45 minutes to an hour and provided an opportunity to examine participant's literacy stories.…”
Section: Data Collectionmentioning
confidence: 99%